2016
DOI: 10.7863/ultra.15.02058
|View full text |Cite
|
Sign up to set email alerts
|

Choice of Formula and Accuracy of Fetal Weight Estimation in Small‐for‐Gestational‐Age Fetuses

Abstract: Objectives The purpose of this study was to identify the most accurate sonographic models for fetal weight estimation in specific subgroups of small‐for‐gestational‐age (SGA) fetuses. Methods We conducted a retrospective study of women who delivered an SGA neonate and underwent a sonographic estimation of fetal weight within 7 days of delivery in a single tertiary center (n = 370). The accuracy of fetal weight estimation was compared for 33 sonographic models (27 nontargeted and 6 targeted SGA– or low‐birth‐we… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
35
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 27 publications
(35 citation statements)
references
References 42 publications
0
35
0
Order By: Relevance
“…Similarly, clinically available tools have various limitations in the estimation of BW, particularly for infants at the two ends of the spectrum of normal BW distribution (i.e., SGA and large for gestational age infants). While the reasons are not well understood, it has been shown that most fetal weight estimation methods perform poorly when dealing with SGA fetuses . Previous studies have shown that methods specifically designed for SGA populations work better than generic ones .…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Similarly, clinically available tools have various limitations in the estimation of BW, particularly for infants at the two ends of the spectrum of normal BW distribution (i.e., SGA and large for gestational age infants). While the reasons are not well understood, it has been shown that most fetal weight estimation methods perform poorly when dealing with SGA fetuses . Previous studies have shown that methods specifically designed for SGA populations work better than generic ones .…”
Section: Discussionmentioning
confidence: 99%
“…While the reasons are not well understood, it has been shown that most fetal weight estimation methods perform poorly when dealing with SGA fetuses . Previous studies have shown that methods specifically designed for SGA populations work better than generic ones . Moreover, even with SGA specific methods, those that consider SGA as a homogeneous group tend to overestimate BW while the opposite trend is observed for SGA sub‐group specific approaches …”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Interestingly, among those with normal Doppler, 45.9 and 13.3% of cases in G1 and G2, respectively, turned out to have a neonatal birth weight superior to that established to be considered FGR [9]. On these subgroups, vaginal delivery rate exceeded 90% on the first group and came close to it on the second.…”
Section: Discussionmentioning
confidence: 99%
“…Other models have been developed in appropriately grown and small‐for‐gestational‐age (SGA) populations and preterm populations but have never been directly compared with one another in an eFGR cohort. Previous research has suggested that the choice of model in an SGA population may depend on other factors, such as gestation, symmetrical/asymmetrical growth or Doppler abnormalities …”
Section: Introductionmentioning
confidence: 99%